A Discourse of Islamic Law on Environmental Protection and Sustanability: How are religious values transferred into Indonesian Environmental Law? - Rohman, Agus Taufiqur; Ibrahim, Aminullah (Indonesian Journal of Environmental Law and Sustainable Development, 2022)
Apart from prohibiting causing damage to the earth, Islam also has an obligation to protect the environment and respect the universe which includes the universe which includes humans, plants, animals, other living things, and non-living things. Preservation of nature and the environment is inseparable from the role of humans, environmental damage is a reflection of the decline in the level of human faith. This study discusses the discourse of Islamic law in environmental protection and environmental sustainability. This study uses a comparative approach and legal interpretation, especially in the context of Islamic law which relates to obligations regarding environmental protection. This study found that, in many literatures and the views of Muslim experts, it is emphasized that protecting the environment is the same as protecting property. God provides humans with treasures to live life on earth, and wealth is not only money, but also earth, trees and plants are treasures. This study highlighted that Quran Surah Al-Araf verse 56, "and do not make any damage on earth after Allah has repaired it and pray to Him with fear and hope. Indeed, Allah's mercy is very close to those who do good”, used as a proof of Islamic values on environmental protection. In this interpretation it is emphasized that this verse is an affirmation of the prohibition of all forms of damage. Therefore, efforts to preserve the environment are not only at the conceptual level, but also manifest in Muslim life.